PELATIHAN PENGOLAHAN DATA BERBASIS STATISTICAL PACKAGE FOR THE SOCIAL SCIENCES BAGI MAHASISWA PENDIDIKAN AKUNTANSI - Nuraisyiah; Sitti Hajerah Hasyim; Abd. Rijal; Nurjannah; Nurdiana (CV. Aksara Global Akademia, 2023)
This training activity aims to train final year students in Accounting Education Study Program Faculty of Economics, State University of Makassar in the processing of statistical data, which includes simple regression analysis, multiple regression, and correlation. The knowledge and skills acquired by the students are expected to be applied in completing the final task. Implementation of statistical data processing training is running smoothly in accordance with the expected by the implementing team. This is shown by the enthusiasm of the trainees in following the materials as well as the given paracels. The success of this activity is caused by several factors: the students of the trainees are familiar with the implementing team so as to facilitate their directing, the training material is very much needed by the students to improve their understanding and ability in statistical data processing. in preparing the final assignment of students. The limitations felt by the implementing team are the supporting facilities in the form of computer owned by the laboratory is not sufficient in terms of quantity. This resulted in training done by adjusting the laboratory conditions, which of course the delivery of material is not optimal